Fibrosing interstitial lung diseases involve different pathogenic pathways with similar outcomes. - Vasakova, Martina; Poletti, Venerino (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Fibrosing interstitial lung diseases (ILDs) are a large group of diseases triggered by external or internal stimuli that can have similar outcomes, i.e. lung fibrosis. Some ILDs are primarily fibro-proliferative disorders in which alveolar loss and epithelial/fibroblastic proliferation and dysplasia lead to lung fibrosis and architectural derangement, while other ILDs are considered inflammatory disorders in which specific underlying conditions (with either an external or an internal origin) can shift the pathogenic process to the fibro-proliferative pathway. The treatment of primarily inflammatory ILDs, regardless of their tendency to switch to lung fibrosis usually consists of anti-inflammatory drugs (e.g. corticosteroids, cytostatic + immunosuppressive agents), targeted ‘biologic treatment’ (e.g. anti TNF-alpha, anti CD20) and combinations thereof. However, we have entered an era in which new drugs that specifically target fibrosing ILDs, namely IPF, have emerged. Continuing laboratory research and clinical studies will hopefully provide us with a more complete understanding of the pathogenesis of fibrosing ILDs. Additionally, we are optimistic about the discovery of new pharmacological targets for the treatment of these serious diseases. The complex issues concerning fibrosing ILDs were addressed and passionately discussed during the Prague postgraduate course and conference devoted to these diseases (June 19th – 21th, 2014).